Assessment of the phytochemical profiles of novel hop (Humulus lupulus L.) cultivars: A potential route to beer crafting. (1st March 2019) - Yan, DanDan; Wong, Yong Foo; Shellie, Robert A.; Marriott, Philip J.; Whittock, Simon P.; Koutoulis, Anthony
Highlights: Phytochemical diversity of 30 Australian hop genotypes was investigated. 58 metabolites were selected across analysed samples; 24 were detected in all samples. Distinct differentiation of 18 hybrids from 12 commercial genotypes was possible. Differences were related to genetic origin or bioaccumulation processes. Abstract: This study investigated the volatile phytochemical diversity of 30 samples obtained from experimental hybrid and commercial H. lupulus L. plants. Essential oils distilled from these samples were analysed by high resolution gas chromatography coupled with accurate mass time-of-flight mass spectrometry (GC–accTOFMS). A total of 58 secondary metabolites, mainly comprising 18 esters, 6 monoterpene hydrocarbons, 2 oxygenated monoterpenes, 20 sesquiterpene hydrocarbons, 7 oxygenated sesquiterpenes, and 4 ketones, were positively or tentatively identified. A total of 24 metabolites were detected in all samples, but commercial cultivars (selected for brewing performance) had fewer compounds identified compared to experimental genotypes. Chemometrics analyses enabled distinct differentiation of experimental hybrids from commercial cultivars, discussed in terms of the different classes of compounds present in different genotypes. Differences among the mono- and sesquiterpenoids, appear to be related to either: i) the genetic origin of the plants; or ii) the processes of bioaccumulation of the identified secondary metabolites.